Effect of Potassium Promoter on Cobalt Nano-catalysts for Fischer-Tropsch Reaction - Ali, Sardar (2012)
In the present work effect of potassium on cobalt nano-catalysts for Fischer-Tropsch reaction has been presented. The catalysts were prepared using a wet impregnation method and promoted with potassium. Samples were characterized by nitrogen adsorption, H2-TPR, and TEM. The Fischer-Tropsch Synthesis (FTS) was carried out in a fixed-bed microreactor 220 °C, 1 atm, H2/CO=2 and a velocity (SV) =12 L/g.h. for 5 h. Addition of potassium into Co/CNTs decreased the average size of cobalt nanoparticles and the catalyst reducibility. Potassium-promoted Co catalyst resulted in appreciable increase in the selectivity of C5+ hydrocarbons and suppressed methane formation. The 0.06%KCo/CNTs catalyst enhanced the C5+ hydrocarbons selectivity by a factor of 23.5% and reduced the methane selectivity by a factor of 39.6%.